Associative memory persistence in 3‐ to 5‐year‐olds. Issue 5 (12th March 2021) - Saragosa‐Harris, Natalie M.; Cohen, Alexandra O.; Shen, Xinxu; Sardar, Haniyyah; Alberini, Cristina M.; Hartley, Catherine A.
Abstract: Adults struggle to recollect episodic memories from early life. This phenomenon—referred to as "infantile" and "childhood amnesia"—has been widely observed across species and is characterized by rapid forgetting from birth until early childhood. While a number of studies have focused on infancy, few studies have examined the persistence of memory for newly learned associations during the putative period of childhood amnesia. In this study, we investigated forgetting in 137 children ages 3–5 years old by using an interactive storybook task. We assessed associative memory between subjects after 5‐min, 24‐h, and 1‐week delay periods. Across all delays, we observed a significant increase in memory performance with age. While all ages demonstrated above‐chance memory performance after 5‐min and 24‐h delays, we observed chance‐level memory accuracy in 3‐year‐olds following a 1‐week delay. The observed age differences in associative memory support the proposal that hippocampal‐dependent memory systems undergo rapid development during the preschool years. These data have the potential to inform future work translating memory persistence and malleability research from rodent models to humans by establishing timescales at which we expect young children to forget newly learned associations. Abstract : Using an interactive associative memory task in children ages 3–5 years old, we establish timescales of memory persistence for newly learned associations during this proposed sensitive period of memory development.